Developing a Chatbot for Process Modelling Learning: contributions for active learning in engineering education - Lopes, Erik Teixeira (2024)
Technological advancements such as generative artificial intelligence (AI) chatbots have gained popularity, partly due to their ability to provide iterative access to extensive information. This has impacted the education field, introducing new opportunities and challenges in learning, teaching, and assessment. This article intends to present the development and deployment of a chatbot designed to foster students’ learning regarding process modelling and Business Process Model and Notation (BPMN). Developed with a low-code tool from the Microsoft suite, this approach for building chatbots may be replicable in other contexts of higher education. This is an exploratory study with 18 students enrolled in a Master’s Program in Engineering and Operations Management. Moreover, 6 professionals with experience in using BPMN used the ChatBot and gave an additional and complementary perspective from an expert point of view. The main objective is to evaluate the effectiveness of the ChatBot to mimic real-world interactions and make a contribution to the learning process. Through this exploration, the article aims to discuss potential uses of the chatbot, exploring the development steps, users’ feedback, limitations, and opportunities for enhancement. This work underscores how emerging technologies facilitate the swift creation of specialized bots for diverse applications, sidestepping the need for intricate programming expertise. More than just enhancing student engagement by encouraging inquiry and the use of AI tools, the use of chatbots has the potential to significantly lighten the teaching load, a cited barrier in the adoption of active learning.